Credit Cycles, Fiscal Policy, and Global Imbalances - Jones, Callum (IMF Working Papers; Working Paper ;, 2021)
We study the role that changes in credit and fiscal positions play in explaining current account fluctuations. Empirically, the current account declines when credit increases, and when the fiscal balance declines. We use a two-country model with financial frictions and fiscal policy to study these facts. We estimate the model using annual data for the U.S. and 'a rest of the world' aggregate that includes main advanced economies. We find that about 30 percent of U.S. current account balance fluctuations are due to domestic credit shocks, while fiscal shocks explain about 14 percent. We evaluate simple macroprudential policy rules and show that they help reduce global imbalances. By taming the financial cycle, macroprudential rules that react to domestic credit conditions or to domestic house prices would have led to a smaller and less volatile U.S. current account deficit. We also show that a countercylical fiscal policy rule that stabilizes output growth reduces the level and volatility of the U.S. current account deficit.